Birka: Regional and Local Topography - Ambrosiani, Björn (Hikuin, 1998)
In the 8th century a number of small specialized settlements grew up around the shores of the Baltic Sea. They acted as focal points for regional and local trade, and as manufacturing centres for the specialized crafts which were becoming ever more important with the expansion of the rural population. It cannot have been easy to select the sites for these markets and harbours, places where foreign merchants and craftsmen could settle and meet the native inhabitants. Along the southern coasts they were usually founded on estuaries, either beside lagoons sheltered from the sea by sand spits or on the sand spits themselves, as at Wolin and Ralswiek. In the exceptional cases where they stood on the open coastline the preferred sites were at the mouths of streams where there were suitable conditions for drawing boats up out of the water. Trelleborg in Scania is a good example of this.